HUBUNGAN BEBAN KERJA DENGAN STRES KERJA TERHADAP KINERJA PERAWAT DI IGD - Marwatus Sholikhah; Joko Prasetyo; Aditya Nuraminudin Aziz (Universitas Pesantren Tinggi Darul Ulum, 2021)
Abstract The nurse is one of the health workers in the hospital who plays an important role in achieving health development goals and the success of health services depends on the participation of nurses in providing quality nursing care in the emergency room for patients because the cause of the patient is uncomfortable and dissatisfied in giving Nursing care services, namely the performance of the nurses themselves and those that can affect the performance of nurses, namely the workload and work stress of nurses such as the number of patients, high work demands, conflicts with coworkers and lack of staff, in the ER and the problem of unsuitable nurse salaries. with its performance. This is to determine the relationship between workload and work stress on the performance of nurses in the ER. The database used in the google scholar review literature that matches the inclusion and exclusion criteria of articles published in 2013-2020 using national and international journals using the Cross Sectional method and the population used by all nurses working in the emergency room. The results found in 10 journals regarding workload and work stress on the performance of nurses in the emergency room which caused performance to decline, suggestions for further researchers to be used as a source of data for further research and to review using the latest theories and using many books in their research.Keywords: Nurse Workload, Nurses work stress, Performance